2018
DOI: 10.1371/journal.pone.0205604
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of antennal sensilla of three fruit borers (Lepidoptera: Crambidae or Tortricidae)

Abstract: Three fruit borers Conogethes punctiferalis (Guenée) (Crambidae), Grapholita molesta Busck (Tortricidae), and Spilonota albicana Motschulsky (Tortricidae) are serious pests of fruit trees. In this study, their antennal morphology, types of sensilla, and distributions were observed by using SEM (Scanning Electron Microscope). Nine types of sensilla were found on the antennae of C. punctiferalis, while eight types of sensilla were presented on each of G. molesta and S. albicana. The sensilla trichodea with two s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 28 publications
(31 reference statements)
5
15
0
Order By: Relevance
“…SS have been widely reported among Lepidoptera, like Agrotis ipsilon Hufnagel, 1766, Plodia interpunctella Hübner, 1813, and Conogethes punctiferalis Guenée, 1854 (Li, Liu, Du, Li, & Wu, ; Ndomo‐Moualeu, Ulrichs, Radek, & Adler, ; Yang et al, ). In this study, SS were observed on antennae of both sexes, covered by scales.…”
Section: Discussionmentioning
confidence: 99%
“…SS have been widely reported among Lepidoptera, like Agrotis ipsilon Hufnagel, 1766, Plodia interpunctella Hübner, 1813, and Conogethes punctiferalis Guenée, 1854 (Li, Liu, Du, Li, & Wu, ; Ndomo‐Moualeu, Ulrichs, Radek, & Adler, ; Yang et al, ). In this study, SS were observed on antennae of both sexes, covered by scales.…”
Section: Discussionmentioning
confidence: 99%
“…Three types of trichoid sensilla were reported to be present in both male and female S. exigua and S. ornithogalli (Jefferson et al, 1970). Sensilla trichoidea is primarily associated with sex pheromone perception (Shneider,1964 andSteinbrecht, 1995) and is sensitive to plant volatiles in female Heliothis virescens (Hillier et al, 2006) and S. litura (Zhang et al, 2013).In fruit borers, Conogethes punctiferalis, Grapholita molesta, and Spilonota albicana, they are involved in the perception of both host plant volatiles and sex pheromones (Li et al, 2018). Sensilla chaetica (SCh) are straight sensillae with a wider base, curved apex and truncated tip.…”
Section: Sensilla Trichoidea (St)mentioning
confidence: 99%
“…As workers and soldiers are blind, they obtain environmental information using antennal sensilla ( Yanagawa et al 2009 ). Antennae are the major sensory and olfactory organs that process a wide range of sensilla types for the treatment of chemical signals, which allow them to survive in different environments ( Bawin et al 2017 , Li et al 2018 , Silva et al 2019 ). The antennal sensilla may play a role in nestmate recognition in workers and soldiers ( Huang et al 2012 ).To perform specialized social interactions, every individual needs chemical communication, which requires a special chemosensory system in the division of labor.…”
mentioning
confidence: 99%